KETERLIBATAN PEREMPUAN DALAM LEMBAGA LEGISLATIF TAHUN 2014-2019 (STUDI KASUS KABUPATEN HALMAHERA UTARA) - Gorahe, Muhammad Guntur Hi Latif; Kusen, Albert W. S.; Pratiknjo, Maria Heny (HOLISTIK, Journal Of Social and Culture, 2018)
The presence of women in Indonesia's political stage, both in the general election national (pemilu) or regional head election (pemilukada) in areas the more looks real. The presence of the figure of the woman could not be denied to have the political dynamics of the coloring. The presence of women in politics in these areas can be described as a new phenomenon, along with the current of democratization that is increasingly strengthened up to these areas. This phenomenon is a tendency that continues to strengthen as a result of the continuing rise of movement and demands, as well as the widespread awareness about gender equality.In the reality of the political situation in North Halmahera are generally women are indeed seen late in his involvement in politics. Stigma-the stigma that women are always in the position of domestic (household) is considered as one of the things that result in women's late start in getting involved in politics. The cultural stigma of this kind brings access to the weakening of the political rights of women in the decision making of strategic-oriented women's interests itself in particular and the public interest. In addition to the reality of cultural stigma that woke up. The factual reality of the domination of men in the institutions of DPRD, were also influential significantly against the weak participation of women in public decision-making processes.North Halmahera has many women active in various areas of life good social, economic or political. Even work that already dozens of years ago only fitting is done by men, currently the work already performed the women of North Halmahera, including grunt work though for example stone, miners and others.When the women who get involved in running as a member of DPRD in North Halmahera Regency there is still a view be r current swell about the struggle to grab the seats of the legislature is expensive. The campaign to the community as well as the political cost that must be removed to a succession of winning elections is not cheap. This is what being a fairly influential factor towards the involvement of women in politics.Keywords: women, participation, political